2017
DOI: 10.1002/mc.22755
|View full text |Cite
|
Sign up to set email alerts
|

BAG3‐dependent expression of Mcl‐1 confers resistance of mutant KRAS colon cancer cells to the HSP90 inhibitor AUY922

Abstract: Past studies have shown that mutant KRAS colon cancer cells are susceptible to apoptosis induced by the HSP90 inhibitor AUY922. Nevertheless, intrinsic and acquired resistance remains an obstacle for the potential application of the inhibitor in the treatment of the disease. Here we report that Mcl-1 is important for survival of colon cancer cells in the presence of AUY922. Mcl-1 was upregulated in mutant KRAS colon cancer cells selected for resistance to AUY922-induced apoptosis. This was due to its increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The antiapoptotic protein Mcl-1 is located in the mitochondria and often leads to drug resistance in solid tumors because of its high expression. In mutant KRAS colon cancer cells, the high expression of Mcl-1 is stabilized by the Bcl-2-associated athanogene domain 3 (BAG3), which is upregulated by the heat shock factor 1 (HSF1) and downstream of XBP1, and HSF1 can cause resistance to the HSP90 inhibitor AUY922 (Wang et al, 2018; Figure 1).…”
Section: Antiapoptotic Genes Of the Bcl-2 Familymentioning
confidence: 99%
See 1 more Smart Citation
“…The antiapoptotic protein Mcl-1 is located in the mitochondria and often leads to drug resistance in solid tumors because of its high expression. In mutant KRAS colon cancer cells, the high expression of Mcl-1 is stabilized by the Bcl-2-associated athanogene domain 3 (BAG3), which is upregulated by the heat shock factor 1 (HSF1) and downstream of XBP1, and HSF1 can cause resistance to the HSP90 inhibitor AUY922 (Wang et al, 2018; Figure 1).…”
Section: Antiapoptotic Genes Of the Bcl-2 Familymentioning
confidence: 99%
“…The targeted regulation of ERS-related regulatory factors and effectors and combining them with antitumor drugs are useful in improving drug sensitivity. For example, since the HSF1/BAG3/Mcl-1 axis can protect mutated KRAS colon cancer cells from AUY922-induced apoptosis, it is of potential significance to target this axis for improving the efficacy of AUY922 in colon cancer treatment (Wang et al, 2018). NF-κB inhibition enhances imiquimod-induced apoptosis of the melanoma cells and reverses chemotherapy resistance (El-Khattouti et al, 2016).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Due to the remarkably increased tendency of chaperone induced by ER-stress response, many studies have targeted chaperone as a therapeutic target. GRP94, as a common chaperone, HSP90 inhibitor geldanamycin and AUY922 causes cell death ( Marcu et al, 2002 ; Wang et al, 2018 ). Strikingly, some of the agents are nonspecific inhibitors with lower toxicity displaying power and selectivity for GRP94 ( Duerfeldt et al, 2012 ).…”
Section: Treatment Of Intestinal Diseases Targeting Er Stressmentioning
confidence: 99%
“…BAG3 has been shown to play a role in the regulation of eIF2a phosphorylation and promote macroautophagy, HDAC6 function, and a transcriptional regulatory in its own right and with heat shock factor 1 (HSF1) [42][43][44][45][46]. The IRE1 ER stress pathway has been proposed to regulate the transcription of BAG3 in part by the regulation of HSF1 [46,47]. Over-expression of GRP78 prevents both the phosphorylation of eIF2a and also activation of the IRE1 ER stress pathway and our data demonstrated that expression of GRP78 almost abolished the drug-induced expression of BAG3.…”
Section: Discussionmentioning
confidence: 99%